Controlling behaviors and lifetime economic, emotional, physical, and sexual violence in Türkiye - Alkan, Ömer; Bayhan, Yağiz Can; Abar, Hayri (Journal of public health, 2025)
Aim The aim of this study is to identify the factors associated with five types of violence (physical, sexual, economic, emotional violence, and controlling behaviors) in which violence against women by an intimate partner is observed intensely in Türkiye. Subjects and methods The study used the cross-sectional data of the “National Research on Domestic Violence Against Women in Türkiye” conducted by Hacettepe University Institute of Population Studies in 2014. The factors associated with physical, sexual, economic, and emotional violence and controlling behavior were identified using multivariate probit regression analysis. Results The prevalence of physical violence, sexual violence, emotional violence, economic violence, and controlling behaviors were found to be 33.66%, 11.08%, 42.72%, 28.78%, and 78.53%, respectively. The findings indicate that city-dwelling, low-income, childbearing women who have experienced physical or sexual violence by someone other than their intimate partner are at risk for intimate partner violence (IPV). It has been determined that women whose intimate partners drink, gamble, cheat on them, and demonstrate aggressive behavior in their social lives are at risk for IPV. In addition, low education levels of both the partner and the woman, as well as a history of domestic violence, were found to increase the risk of intimate partner violence. Conclusions It has been determined that the prevalence of various forms of intimate partner violence in Türkiye is quite high. Even though almost eight out of ten women are exposed to controlling behaviors, this does not come to the fore, suggesting that these behaviors are perceived as normal behaviors in the Turkish population. Therefore, more in-depth research must be conducted on controlling behaviors in Türkiye. In addition, the prevalence of physical, sexual, emotional, and economic violence has been determined to be high. Given that the types of violence are interrelated, we think that various measures should be taken to prevent women who are exposed to controlling behaviors from experiencing other forms of violence in the future.